ESTABLISHING SHOLAWAT THROUGH HADRAH ART ACTIVITIES IN MADRASAS - Astutik, Astutik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is an effort to continue to increase prayer for the Prophet Muhammad SAW in the hope of obtaining intercession in the afterlife and also to strive to seek the pleasure of the Prophet Muhammad SAW after the pleasure of Allah SWT. Praying to the Prophet can provide many benefits, including reassuring the heart and eliminating sadness. This research is qualitative research using observation, interviews and documentation as data collection techniques. The subjects of this research were all residents of the MI Nurul Mun'im school. From the results of this research, it can be concluded that reciting prayers through the art of hadrah makes the soul feel calmer, the spirit of prayer returns because it uses modern tones, and increases our devotion to Rasulullah SAW. However, there are some students who are less enthusiastic about reading the prayers that have been sung.